2014
DOI: 10.1089/jwh.2013.4598
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Vitamin D with Symptoms of Depression and Anxiety in Early Pregnancy

Abstract: Objective: To evaluate associations between early pregnancy 25-hydroxyvitamin D (25[OH]D) concentrations and antepartum depression and anxiety symptoms and potential modifiers thereof. Materials and Methods: In a pregnancy cohort (N = 498), we examined cross-sectional associations of early pregnancy (mean = 15.4 weeks gestation) serum 25[OH]D concentrations and depression and anxiety symptoms. Symptoms were measured using Depression, Anxiety, and Stress Scales (DASS-21) and Patient Health Questionnaire Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 44 publications
2
90
1
1
Order By: Relevance
“…Huang et al recruited 498 women in their early gestation for a study and assessed the relation between vitamin D and depression and anxiety. Results showed that with a 1ng/mL decrease in 25[OH] D, the risk of anxiety and depression increased by 0.043 and 0.040 (p-values=0.052 and 0.029, respectively) [26]. The results of Huang et al are in line with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Huang et al recruited 498 women in their early gestation for a study and assessed the relation between vitamin D and depression and anxiety. Results showed that with a 1ng/mL decrease in 25[OH] D, the risk of anxiety and depression increased by 0.043 and 0.040 (p-values=0.052 and 0.029, respectively) [26]. The results of Huang et al are in line with our study.…”
Section: Discussionsupporting
confidence: 91%
“…However, in several past studies, a reverse relationship was detected between maternal 25-hydroxyvitamin D level and AND (17,43). It is worth mentioning that most of the current participants had vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 69%
“…Associations between vitamin D concentration and cognitive decline measured by the mini‐mental state examination have been reported among older adults . As well as associations between vitamin D concentration and depression established by a patient health questionnaire, among older men and pregnant women ; among young adult men, assessed using the 21‐item Depression Anxiety Stress Scales , overweight women assessed by Hospital Anxiety and Depression questionnaire , and in adults with a history of depression, defined by a Center for Epidemiologic Studies Depression Scale score . But no association was found in a population of young women, assessing depression by the Beck Depression Inventory questionnaire .…”
Section: Discussionmentioning
confidence: 99%